Temperature control for a muffle oven using the PLC Moller Ec4p-200 (2013)
This report presents the design and implementation of a temperature control system in a muffle oven belonging to the coal laboratory of UPTC Sogamoso. We use the PLC EC4P didactic module of the Industrial Automation Laboratory of the School of Electronic Engineering from the same institution. This paper describes the procedure performed using the elements of the module, such as the PLC Moller EC4P-200, HMI touch screen and temperature universal transmitters to adjust the signal from the type K thermocouple which is the sensor used to measure the temperature inside of the muffle. Besides, it isshown the system modeling and the design of a PID controller as well as the obtained results of the controller implementation on the oven.